Novel Fiber-Optic Ring Acoustic Emission Sensor - Peng Wei; Xiaole Han; Dong Xia; Taolin Liu; Hao Lang (Sensors, 2018)
Acoustic emission technology has been applied to many fields for many years. However, the conventional piezoelectric acoustic emission sensors cannot be used in extreme environments, such as those with heavy electromagnetic interference, high pressure, or strong corrosion. In this paper, a novel fiber-optic ring acoustic emission sensor is proposed. The sensor exhibits high sensitivity, anti-electromagnetic interference, and corrosion resistance. First, the principle of a novel fiber-optic ring sensor is introduced. Different from piezoelectric and other fiber acoustic emission sensors, this novel sensor includes both a sensing skeleton and a sensing fiber. Second, a heterodyne interferometric demodulating method is presented. In addition, a fiber-optic ring sensor acoustic emission system is built based on this method. Finally, fiber-optic ring acoustic emission experiments are performed. The novel fiber-optic ring sensor is glued onto the surface of an aluminum plate. The 150 kHz standard continuous sinusoidal signals and broken lead signals are successfully detected by the novel fiber-optic ring acoustic emission sensor. In addition, comparison to the piezoelectric acoustic emission sensor is performed, which shows the availability and reliability of the novel fiber-optic ring acoustic emission sensor. In the future, this novel fiber-optic ring acoustic emission sensor will provide a new route to acoustic emission detection in harsh environments.